Qui étaient les Attikamègues? - Clermont, Norman (Anthropologica, 2022)
This paper presents a systematic collection of information to be found in 17th century documents which spoke of the Attikamegue. The Attikamegue were a nomadic Cree-Montagnais tribe living North of the St. Lawrence River in Quebec. In the 17th century they consisted of approximately 550 members divided into three bands which were socially independant. The main traits of their culture were essentially similar to those of the other boreal forest groups. They seem to haven disappeared around 1670-80.